Octahedral Distortions at High‐Temperature Superconducting La2CuO4 Interfaces: Visualizing Jahn–Teller Effects. Issue 24 (4th December 2017) - Suyolcu, Y. Eren; Wang, Yi; Sigle, Wilfried; Baiutti, Federico; Cristiani, Georg; Logvenov, Gennady; Maier, Joachim; van Aken, Peter A.
Abstract: Tuning the octahedral network represents a promising route for achieving new properties and functionalities in perovskite‐based oxide heterostructures. One of the interface‐mediated phenomena occurring in complex oxides is the Jahn—Teller (JT) effect. With the purpose of investigating octahedral distortions at interfaces showing high‐temperature interface superconductivity, atomic layer‐by‐layer oxide molecular‐beam epitaxy grown bilayers consisting of three unit cells, overdoped metallic La1.6 M0.4 CuO4, and three unit cells undoped insulating La2 CuO4, where M represents a divalent dopant (namely, Ba 2+, Sr 2+, and Ca 2+ ), are studied. The local crystal structure, chemistry, and dopant distribution are probed by analytical spherical‐aberration‐corrected scanning transmission electron microscopy. Here, the interrelation between the cationic size mismatch between dopant (M 2+ ) and host La 3+ ions and the local structure are reported, and the impact of the dopant distribution on the structural (CuO6 octahedra elongation) local properties is discussed. A clear correlation between dopant size and local lattice deformations is highlighted. Moreover, a relation between the nature of superconductivity (bulk vs interface) and JT distortions of the anionic sublattice is suggested. Abstract : Scanning transmission electron microscopy ‐based quantitative investigations of octahedral distortions in atomic layer‐by‐layer oxide molecular beam epitaxy grown La1.6 M0.4 CuO4 /La2 CuO4 bilayers with M = Ba, Sr, and Ca are carried out. It is reported that the dopant distribution remarkably influences the apical OO distances (i.e., Jahn–Teller and anti‐Jahn–Teller effects) and the superconducting properties of La2 CuO4 systems.